2015
DOI: 10.4018/978-1-4666-8611-3.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Is M-PESA a Model for Financial Inclusion and Women Empowerment in Kenya?

Abstract: Since the 1980s, the gender gap in most countries—rich and developing—has been narrowing. Women and girls are going to school more, living longer, getting better jobs, and acquiring legal rights and protections. Despite these strides, women in poor rural communities remain financially excluded from formal financial services. This chapter explores the impact of mobile banking on financial inclusion and women's empowerment in Kenya. The aim is to evaluate whether mobile banking is a form of financial inclusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Despite the evidence provided in the above research papers on the impact of FinTech on reducing poverty, some researchers have found that the link between the use of mobile money specifically and poverty alleviation is weak (Aron, 2018; Collins and Ng'weno, 2018). Others argue that historical successes of mobile technology in East Africa cannot be generalized to other regions since the adoption of technological innovation depends on institutional endowments and the pace of innovation depends on government regulations and its ability to spillover the benefits to other sectors (Barasa and Lugo, 2015; Mbiti and Weil, 2015; Arabéhéty, 2016; Johnson, 2016; Minto-Coy and McNaughton, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the evidence provided in the above research papers on the impact of FinTech on reducing poverty, some researchers have found that the link between the use of mobile money specifically and poverty alleviation is weak (Aron, 2018; Collins and Ng'weno, 2018). Others argue that historical successes of mobile technology in East Africa cannot be generalized to other regions since the adoption of technological innovation depends on institutional endowments and the pace of innovation depends on government regulations and its ability to spillover the benefits to other sectors (Barasa and Lugo, 2015; Mbiti and Weil, 2015; Arabéhéty, 2016; Johnson, 2016; Minto-Coy and McNaughton, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides the addition of a moderating variable, this current study was also conducted in a rural Bangladesh area which has not received much attention from previous studies as posited by previous researchers: Belayeth Hussain et al [16] , Hussain and Jullandhry [18] , George and Thomachan [56] , Hussain and Haque [57] , where most studies on the same variables were conducted in the US or other developed countries. Considering the suggestions from Barasa & Lugo [15] , Hendriks [17] , Siddik [19] , Bangladesh was chosen as it is a developing country, and limited studies have been done on the effect of financial inclusion on women's empowerment in this region. Therefore, this study bridges the gap in the current field of research outside the western nation.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Despite the inconsistent findings of recent research on the current field, compelling reasons exist to prioritize this issue for both instrumental and intrinsic motivations. At the same time, there is evidence that women's empowerment increases when they have access to financial resources [6,[15][16][17][18][19] . However, some studies have discovered an inconsistent relationship between financial inclusion and women empowerment [20,21] ; while Neaime and Gaysset [22] found that financial inclusion has no discernible effect on poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the usage of mobile money requires both the sender and receiver to have access to a mobile phone and have the digital literacy to use the service. While recent literature has explored the extent to which digital literacy and access to a mobile phone limits the access of vulnerable populations to mobile money in developing countries, less is known about the extent to which transaction fees affect the transaction behaviour of vulnerable populations (Van Hove and Dubus, 2019;Wyche et al, 2016;Barasa and Lugo, 2015).…”
Section: Introductionmentioning
confidence: 99%